Los valencianos del Cancionero general : estudio de sus poesías - Pérez Bosch, Estela; Castillo, Hernando del (Colección Parnaso ;, 2009)
Cancionero general, compiled by Hernando del Castillo in 1511 in the city of Valencia, is a major and important summary of Castillian poetry of the 15th and 16th century.